The Impact of Morphological Awareness on Word Reading and Dictation in Chinese Early Adolescent Readers With and Without Dyslexia - Kalindi, Sylvia Chanda; Chung, Kevin Kien Hoa (Frontiers in Psychology, 2018)
This study investigated the role of morphological awareness in understanding Chinese word reading and dictation among Chinese-speaking adolescent readers in Hong Kong as well as the cognitive-linguistic profile of early adolescent readers with dyslexia. Fifty-four readers with dyslexia in Grades 5 and 6 were compared with 54 chronological age-matched (CA) typical readers on the following measures of cognitive-linguistic and literacy skills: morphological awareness, phonological awareness, visual-orthographic knowledge, rapid naming, vocabulary knowledge, verbal short-term memory (STM), Chinese word reading, and dictation (or spelling). The results indicated that early adolescent readers with dyslexia performed less well than the typical readers on all cognitive-linguistic and literacy measures except the phonological measures. Both groups' scores showed substantial correlations between morphological awareness and Chinese word reading and dictation. Visual-orthographic knowledge and rapid naming were also associated with dictation in early adolescent readers with and without dyslexia, respectively. Moderated multiple regression analyses further revealed that morphological awareness and rapid naming explained unique variance in word reading and dictation for the readers with dyslexia and typical readers separately after controlling readers' age and group effect. These results highlight the potential importance of morphological awareness and rapid naming in Chinese word reading and writing in Chinese early adolescents' literacy development and impairment.